Understanding and managing uncertainty and variability for wastewater monitoring beyond the pandemic: Lessons learned from the United Kingdom national COVID-19 surveillance programmes - Wade, Matthew J.; Lo Jacomo, Anna; Armenise, Elena; Brown, Mathew R.; Bunce, Joshua T.; Cameron, Graeme J.; Fang, Zhou; Farkas, Kata; Gilpin, Deidre F.; Graham, David W.; Grimsley, Jasmine M.S.; Hart, Alwyn; et al. (Journal of hazardous materials, 2022)
The COVID-19 pandemic has put unprecedented pressure on public health resources around the world. From adversity, opportunities have arisen to measure the state and dynamics of human disease at a scale not seen before. In the United Kingdom, the evidence that wastewater could be used to monitor the SARS-CoV-2 virus prompted the development of National wastewater surveillance programmes. The scale and pace of this work has proven to be unique in monitoring of virus dynamics at a national level, demonstrating the importance of wastewater-based epidemiology (WBE) for public health protection. Beyond COVID-19, it can provide additional value for monitoring and informing on a range of biological and chemical markers of human health. A discussion of measurement uncertainty associated with surveillance of wastewater, focusing on lessons-learned from the UK programmes monitoring COVID-19 is presented, showing that sources of uncertainty impacting measurement quality and interpretation of data for public health decision-making, are varied and complex. While some factors remain poorly understood, we present approaches taken by the UK programmes to manage and mitigate the more tractable sources of uncertainty. This work provides a platform to integrate uncertainty management into WBE activities as part of global One Health initiatives beyond the pandemic. [Display omitted] •Wastewater is a relatively unbiased medium transporting multiple markers of human health.•Biological- and chemical-based Wastewater-Based Epidemiology provides flexibility and resilience for public health security.•Measurements of target analytes in wastewater are subject to variability and uncertainty.•Identifying and mitigating uncertainty requires multi-disciplinary collaboration.•UK wastewater monitoring programmes have generated a substantial data resource to derive better understanding of uncertainty.